Relation of personality status in the delinquent group to the type of accentuation - Suslavičius, A.; Jucevičiūtė, L. (Psichologija, 1987)
The present paper considers the problem of personality status attainment in informal groups of antisocial behaviour. It is aimed at assessing the influence of the accentuation type on the process of status attainment. The questionnaire compiled by A. Lichko, and a sociometric test were used. The subjects were 30 inmates of the 2nd vocational technical school in Vilnius. The status of a person in the group and the type of his accentuation were established. The clearly expressed link between personality status and the type of accentuation was observed only in the class of leaders. No unequivocal link between other positions of status hierarchy and accentuation type has been determined. The applied aspects of the problem are discussed.
Keywords: Personality Status; delinquent group; type of accentuation